Childhood Predictors of Adult Criminality: A Meta-Analysis Drawn from the Prospective Longitudinal Literature - Chiodo, Debbie (2008)
Sufficient research now exists in the psychology of criminal conduct literature to address the long-term impact of early childhood and adolescent experiences on later adult outcomes. In the present meta-analysis, selected studies were prospective and longitudinal, tracking a variety of early childhood and family factors that could potentially predict later involvement in the adult criminal justice system. Thirty-eight studies met the selection criteria. Major findings indicate that dynamic versus static predictors are related to later adult criminal justice involvement. The older the child was at the time the predictor was measured, the stronger was the relationship to adult offending. Within the set of dynamic predictors, childhood and adolescent factors that rate most highly include a variety of behavioural concerns including early identification of aggression, attentional problems, motor restlessness, and attention seeking. Emotional concerns consistent with depression including withdrawal, anxiety, self-deprecation, and social alienation are also represented. Predictors also included family descriptors such as a variety of negative parenting strategies including coerciveness, authoritarian behaviours, lack of child supervision, and family structure variables such as witnessing violence, inter-parental conflict, family stressors, and poor communication. Results are discussed in relation to prevention strategies for targeted services that influence the probability of antisocial outcomes for children into adulthood